Power generation, operation, and control - Wood, Allen J.; Wollenberg, Bruce F. (John Wiley & Sons, Inc., 2013)
Since publication of the second edition, there have been extensive changes in the algorithms, methods, and assumptions in energy management systems that analyze and control power generation. This edition is updated to acquaint electrical engineering students and professionals with current power generation systems